Analysis of issues and solutions on the implementation of istibdal waqf property in states of Peninsular Malaysia - Muhamad Rozaimi Ramle (Tanjung Malim, 2023)
Analysis of issues and solutions on the implementation of istibdal waqf property in states of Peninsular Malaysia by Muhamad Rozaimi Ramle